Effects of an Automated External Defibrillator With Additional Video Instructions on the Quality of Cardiopulmonary Resuscitation - Ettl, Florian; Fischer, Eva; Losert, Heidrun; Stumpf, Dominik; Ristl, Robin; Ruetzler, Kurt; Greif, Robert; Fischer, Henrik (Frontiers in Medicine, 2021)
Aim of the study: The aim was to compare cardiopulmonary resuscitation (CPR) quality of an automated extern defibrillator (AED) with and without additional video instruction during Basic Life Support by laypersons. Methods: First-year medical students were randomized either to an AED with audio only or audio with additional video instructions during CPR. Each student performed 4 minutes of single-rescuer chest-compression only BLS on a manikin (Ambu Man C, Ballerup, Denmark) using the AED. The primary outcome was the effective compression ratio during this scenario. Effective compression ratio is defined as effective compression ratio (compressions with correct depth, correct hand position and complete decompression) multiplied by flow time (active CPR time). Secondary outcomes were other CPR quality and time related parameters and subjective assessments. Results: Effective compression ratio did not differ between study groups in the overall sample (p= 0.337) or in students with (p=0.953) or without AED experience (p=0.278). Additional video instruction led to higher percentage of incorrect decompressions (p=0.014). No significant differences could be detected in time related resuscitation parameters. Additional video was subjectively rated as more supporting (p=0.001). Conclusions: Audio-video instructions did not significantly improve resuscitation quality in these lay persons despite it was felt more supportive. Additional video to the verbal AED prompts might lead to cognitive overload. Therefore, future studies might target the influence of the video content, and potential benefits of video instructions in specific populations.